Data supporting: 'Modelling and optimising hybrid process of wire arc additive manufacturing and high-pressure rolling' - Gornyakov, Valeriy; Sun, Yongle; Ding, Jialuo; Williams, Stewart W. (Cranfield University, 2022)
Figure 7 Predicted distortion of the WAAM part after deactivation of clamps . Figure 8 Longitudinal RS distributions along the vertical path in the symmetry plane for the full-length mechanical models after clamps deactivation, compared to experimental measurements [5]. The flat roller (a) and slotted roller (b) were used in the rolling simulations, and the full-length model was based on the solution mapped from the steady-state region of the reduced-length WAAM + IL rolling model Figure 10 Concurrent evolution of temperature and longitudinal stress (a), as well as the longitudinal PS (b), in the layer 6 during WAAM deposition of layers 6-8 in conjunction with IL rolling using the flat roller. The data were collected at the top of layer 6 in the inspection plane and the rolling phases are highlighted in the yellow shaded areas. Figure 11 Concurrent evolution of temperature and longitudinal stress (a), as well as longitudinal PS (b), in the layer 6 during WAAM deposition of layers 9-11 in conjunction with IL rolling using the flat roller. The data were collected at the top of layer 6 in the inspection plane and the rolling phases are highlighted in the yellow shaded areas. Figure 12 Concurrent evolution of temperature and longitudinal stress (a), as well as longitudinal PS (b), in the layer 6 during WAAM deposition of layers 12-14 in conjunction with IL rolling using the flat roller. The data were collected at the top of layer 6 in the inspection plane and the rolling phases are highlighted in the yellow shaded areas. Figure 13 Concurrent evolution of the longitudinal PS and stress in the layer 9 during WAAM deposition of layers 9-16 in conjunction with IL rolling using the slotted roller. The data were collected at the top of layer 9 in the inspection plane (the slotted roller started rolling on layer 6) and the rolling phases are highlighted in the yellow shaded areas. Figure 18 Evolution of longitudinal PS in the layer 6 during WAAM deposition and stacked 4L rolling with flat roller. The rolling phases are highlighted in the yellow shaded areas.
Keywords: 'Directed energy deposition'; 'Cold working'; 'Residual stress'; 'Distortion'; 'Numerical simulation'